Radiographic evaluation of the tunnel position in single and double bundle anterior cruciate ligament reconstruction - Michele Losco; Francesco Giron; Luca Giannini; Pierlugi Cuomo; Roberto Buzzi; Stefano Giannotti; Nicola Mondanelli (Medicinski glasnik, 2020)
Aim: To evaluate tunnel positioning on radiographs in singlebundle (SB) and double-bundle (DB) anterior cruciate ligament (ACL) reconstruction, to evaluate if measurement is accurate and reproducible. Methods: Radiographs of 30 SB and 30 DB ACL reconstruction were reviewed by two examiners who measured tunnel positioning with the quadrant method on the femur (a=depth, b=height) and the Amis and Jakob method on the tibia. Intra- and inter-observer reliability were evaluated with intra-class correlation coefficient (ICC). Results: A radiographic analysis was completed in all patients in a SB-group and in 27 in a DB-group (p>0.05). Intra-observer reliability was almost perfect on femoral (ICC: a=0.85, b=0.83) and tibial (ICC=0.87) side in the SB-group. In the DB-group, it was almost perfect for tibial anteromedial (AM) and posterolateral (PL) bundles (ICC: AM=0.84, PL=0.81) and for femoral PL bundle (ICC: a=0.83, b=0.82), and substantial for femoral AM bundle (ICC: a=0.78, b=0.74). Inter-observer reliability was almost perfect on tibial (ICC=0.81) and femoral (ICC: a=0.81, b=0.87) side in the SB-group, and substantial on tibial (ICC: AM=0.71, PL=0.77) and femoral (ICC: AM a=0.73, b=0.78; PL a=0.74, b=0.76) side in the DB-group. Standard deviation (SD) was low (±9%) with respect to the centre of tunnel(s). Conclusion: The quadrant method and the Amis and Jakob method are accurate and reproducible measurement methods. Also, as SD was low, an outside-in approach with a front-entry guide, which is free-hand positioned, can be postulated as a reliable method to locate the femoral tunnel in SB reconstruction and the AM bundle in DB reconstruction.
Keywords: anatomic reconstruction; quadrant method; radiographic analysis; tunnel placement